(untitled) (International Journal of Engineering and Computer Science, 2015)
-Mobile Ad hoc networks (MANET) carried out multi-hop communication in an environment with no fixed infrastructure, by means of mobile nodes and changing network topology. In mobile ad hoc networks (MANETs), nodes move freely and so the topology of the nodes is highly dynamic. The process of routing the data packets to the destination is a challenging task.Provoked by this issue, this paper presents the new approach a Dynamic Position Based Routing (DPRP) protocol which implemented in the distributed architecture and takes advantage of the stateless property of geographic routing and the broadcast nature of wireless medium dynamically.In the case of communication hole, a Virtual Destination-based Void Handling (VDVH) scheme is further proposed to work together with DPRP. Both theoretical analysis and simulation results show that DPRP achieves excellent performance even under high node mobility with acceptable overhead and the new void handling scheme also works well.